Education and health behavior of patients with gastric ulcer - Agnieszka Zastawna; Bożena Baczewska; Robert Jan Łuczyk; Alina Dzirba (Kazimierz Wielki University, 2017)
Ulcer disease is one of the most common gastrointestinal condition. The aim of the work is to prove the need for education concerning this disease and to present the lifestyle and health behavior of a person suffering from this condition. The method of case study was used in this study. The author used a questionnaire survey and interview technique, observation and analysis of patient documentation. The results of our research were compared with those of other Polish authors dealing with the topic. The results outline the patient's knowledge of general illness and proper diet; as well as engaging unhealthy behaviors, despite having sufficient knowledge concerning healthy lifestyle.